2014
DOI: 10.4012/dmj.2014-087
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasma and ultraviolet treatment of zirconia on initial attachment of human oral keratinocytes: Expressions of laminin γ2 and integrin β4

Abstract: Initial attachment of human oral keratinocytes cultured on yttria-stabilized tetragonal zirconia polycrystal (TZP) surfaces that were subjected to UV or oxygen plasma (O2-plasma) treatment was investigated. The viability of the attached cells, mRNA expression of laminin γ2 and integrin β4, distribution of laminin γ2 and integrin β4, cell area, and cell morphology were assessed. The results showed that no differences in the viability of attached cells were recognized among the conditions. However, expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…Plasma irradiation increases surface hydrophilicity by reducing the contact angle (23)(24)(25) and increases cell attachment to the irradiated surface.…”
Section: Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma irradiation increases surface hydrophilicity by reducing the contact angle (23)(24)(25) and increases cell attachment to the irradiated surface.…”
Section: Originalmentioning
confidence: 99%
“…Quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) assay Cells on the zirconia disks (n = 3) in the control and treatment groups were lysed at each time point (6,24, and 48 h after seeding), to collect mRNA (NucleoSpin RNA, Machery-Nagel, Dueren, German) and convert it to cDNA with reverse transcriptase (GoScript Reverse Transcription System, Promega), in accordance with the manufacturer's protocol. A microvolume UV-vis spectrophotometer (SimpliNano, GE Healthcare Life Sciences, Buckinghamshire, UK) was used to measure absorbance of mRNA and cDNA samples.…”
Section: Cell Attachment On Disksmentioning
confidence: 99%
“…For example, the oxygen plasma technique is also known to produce a superhydrophilic zirconia surface. Kobune et al [60] reported that oxygen plasma treatment of zirconia promoted the initial attachment of oral keratinocytes by enhancing extracellular matrix components such as laminin γ2 better than UV treatment. Oxygen plasma treatment of blastedHF zirconia implants may provide different results.…”
Section: Discussionmentioning
confidence: 99%
“…Superhydrophilic surface treatment enhances the initial attachment of osteoblast-like cells 8 and oral keratinocytes 9 . The initial attachment and colonization of periodontal pathogenic bacteria on the surfaces of TZP were the same as were those on the titanium surfaces.…”
Section: Discussionmentioning
confidence: 99%